Numerical Simulation of Spacecraft Charging Attributed to Ionospheric Plasma in Polar and Equatorial Environment - Nizam Ahmad; Hideyuki Usui (Faculty of Geography, Universitas Gadjah Mada, 2020)
The presence of spacecraft in ionospheric plasma can change plasma properties, vice versa plasma can lead to charge buildup on spacecraft. The level of charging, through electric potential of spacecraft, initially depends on plasma density. However, simulations done on four LEO satellites, i.e. ERS 1, MIDORI, ASCA and FUSE 1, showed that charging level depends on plasma electron temperature rather than plasma density which satisfied the Boltzmann’s relation in the absence of high-energy electrons from aurora. The higher the plasma electron temperature the more spacecraft exposed to negative charging. It is assumed that plasma ions and electrons are collisionless or in Maxwellian distribution. It is found that there is no strong relation between density and charging level. Furthermore, there exists insignificant different of charging between polar and equatorial satellites. It means that the placement of satellite in polar or equatorial region, as long as the presence of auroral electrons is excluded, will suffer similar level of charging which is less than 5V (negative). Since spacecraft are exposed to negative charge, electric field generated by spacecraft potential, together with mesothermal motion effects, deflects ion trajectory into donwstream region leading to ion void region. The ion density is reduced compared to electron density, but there is no significant different of ion void feature between polar and equatorial satellites.and capacity building of beneficiaries.